The child : infants, Children, and adolescents - Cobb, Nancy J. (London : Mayfield Publishing company, 2001)
Presented with a research base, the self-contained chapters in this book offer teaching flexibility, supporting either a chronological or topical approach. The pedagogical features include chapter narratives, overviews and summaries, stop and think questions, and boxes highlighting research and social policy
Includes bibliographical references and indexes.
Keywords: child psychology; child development